A cristologia na evangelii gaudium do Papa Francisco : uma abordagem pastoral da pessoa de Jesus Cristo - Müller, Paulo Eduardo (2019)
This dissertation deals with Christology present in the Apostolic Exhortation Evangelii Gaudium, by Pope Francis. Through analyzing the content of the Exhortation, he aims to discover the Christ present in the Pope's thought, and to make a connection with his life, his discourses, his practices and to situate him from his entire pastoral approach. For Francis, the encounter with the Lord fills the life of joy and, putting on the person of His Spirit, makes it possible to go to meet others, as Jesus did. The path proposed by the Pope has its reference in the Gospel. It condemns a society that acts and lives without God. He sees in mercy the key to the transformation of society and acting in favor of the neighbor the way to obtain salvation. For Francis an authentic faith is related to a life committed to the good of all people. This implies looking at and understanding each one from your reality and desiring everyone to have life and life in abundance.